Proceedings of the 5th International Conference on Movement and Computing 2018
DOI: 10.1145/3212721.3212812
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Visualization of Movement Qualities in Contemporary Dance

Abstract: Analyzing and documenting contemporary dance movement data has proven to be a very difficult task due to the vast existence of styles and aesthetics which are characteristic of each individual choreographer. Indeed, identifying movement qualities with the intention of co-relating them to specific meanings and choreographic intentions is practically impossible without taking an artist-driven approach. Moreover, equipping dancers with wearable technology in order to accurately track each of their movements is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…In a computer-assisted environment it would be natural to investigate the possibilities to apply movement visualization techniques (Kyan et al, 2015) of virtual reality models, for example such as reported in (Anjos, Ribeiro & Fernandes, 2018). While these techniques excel in guiding precise physical movements, their application to pronunciation training requires overcoming the disjuncture between the kinesthetics of dance and the cadence of spoken language.…”
Section: Towards Integration With a Capt System: Expectation And Chal...mentioning
confidence: 99%
“…In a computer-assisted environment it would be natural to investigate the possibilities to apply movement visualization techniques (Kyan et al, 2015) of virtual reality models, for example such as reported in (Anjos, Ribeiro & Fernandes, 2018). While these techniques excel in guiding precise physical movements, their application to pronunciation training requires overcoming the disjuncture between the kinesthetics of dance and the cadence of spoken language.…”
Section: Towards Integration With a Capt System: Expectation And Chal...mentioning
confidence: 99%